Intelligent Agent For Weather Notification - Jumilah, Abdul Rahman (2003)
Intelligent Agent-for Weather Notification (WPA) is one of the personal assistant agent application that provide notification service to user for monitoring and alerting of weather conditions. Weather is an important event in human daily life and they need to know about the weather event before they pursuit their activities. Three agents have been developed and the functions are checking and retrieving weather forecast on Web site, handle simple tasks of scheduling events and notify the user about the weather events. In this application, the agents are named UserNotificationAgent, WeatherReaderAgent and SchedulerAgent. Borland JBuilder5 was used to develop the Intelligent Agent For Weather Notification application.